Restaurant Quality and Customer Satisfaction - Almohaimmeed, Bader M.A. (International Review of Management and Marketing, 2017)
This study aimed to explore the impact of restaurant quality on customer satisfaction. Restaurant quality was measured using 11 dimensions related to halal, food, hygiene, menu and atmospheric quality, as well as assurance, accuracy, responsiveness, interior design, external environment and price. The sample consisted of 289 respondents randomly selected from 100 small (70) and large (30) full-service restaurants in Saudi Arabia. A questionnaire containing 33 items was developed based on a review of the literature to collect the required data. Based on the dimensions of restaurant quality selected, 11 hypotheses were proposed, all of which are supported. The findings show that all the restaurant quality dimensions examined have a significant and positive influence on customer satisfaction. Moreover, it can be concluded that halal quality is unquestionably influential as none of the restaurants serve prohibited foods. However, other dimensions are also very important, particularly food quality (taste, freshness of meals and amount of food), hygiene (clean dining area and clean staff), responsiveness (prompt service) and menu (display, variety and knowledge of items). As the study was carried out in full-service restaurants, the results cannot be generalized to all types of restaurants, such as fast-food or self-service restaurants. Therefore, future research should consider a larger sample size and different types of restaurant. Keywords: restaurant quality, customer satisfaction, full-service restaurants, service quality JEL Classifications: L1, L83